(untitled) (Colección, 2018)
“How One Becomes what One is” “is Pindaro’s motto is also what unifies Ortega’s philosophy and biography because it is a link, both ethical and vital, between the self and the world. That link is technically called ‘vocation’ and in Ortega’s late philosophy it is the only source of meaning for one’s life. Ortega’s most decisive vocation was of an intellectual-philosopher, in the Socratic-Platonic sense, not of the intellectual as a figure that intervenes in the public sphere, even if he did take on that role with great intensity until 1932-33. Since the outbreak of the Spanish Civil War he decided not to take a public stance in political matters. One of the texts where he reflects deeply about the condition of the intellectual in the roles mentioned above is “El intelectual y el otro” (1940), a text where he establishes a dialogue with circumstances in Argentina for which the text was written, and which had great repercussions in the world of the Republican exiles living in Hispanic America, especially in Mexico.